Le Trône de Grâce : étude et la restauration d’une Trinité lorraine du XVe siècle - Muriel Oiry (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The restoration of the Trône de Grâce including to a diploma of the end of studies was the opportunity to realize the remove of the twelve overpaints recovering the the original polychromy layer. This intervention, long and delicate, was all the more difficult as the sculpture was covered with hardened black crusts. Only an accurate examination makes it possible to document the different paint layers. The various surfaces to be treated, according to their state of preservation.